Combined inactivation of pRB and hippo pathways induces dedifferentiation in the Drosophila retina. - Brandon N Nicolay (PLoS Genetics, 2010)
Functional inactivation of the Retinoblastoma (pRB) pathway is an early and obligatory event in tumorigenesis. The importance of pRB is usually explained by its ability to promote cell cycle exit. Here, we demonstrate that, independently of cell cycle exit control, in cooperation with the Hippo tumor suppressor pathway, pRB functions to maintain the terminally differentiated state. We show that mutations in the Hippo signaling pathway, wts or hpo, trigger widespread dedifferentiation of rbf mutant cells in the Drosophila eye. Initially, rbf wts or rbf hpo double mutant cells are morphologically indistinguishable from their wild-type counterparts as they properly differentiate into photoreceptors, form axonal projections, and express late neuronal markers. However, the double mutant cells cannot maintain their neuronal identity, dedifferentiate, and thus become uncommitted eye specific cells. Surprisingly, this dedifferentiation is fully independent of cell cycle exit defects and occurs even when inappropriate proliferation is fully blocked by a de2f1 mutation. Thus, our results reveal the novel involvement of the pRB pathway during the maintenance of a differentiated state and suggest that terminally differentiated Rb mutant cells are intrinsically prone to dedifferentiation, can be converted to progenitor cells, and thus contribute to cancer advancement.